Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 50. Beitrag. Hymenoptera: Apidae II (Genus Andrena Fabricius). - Warncke, Klaus (Contributions to Entomology = Beiträge zur Entomologie, 1966)
This paper, based on the material of the expedition to Albania by Deutsches Entomo- logisches Institut, compiles all species of the Apidae genus Andrena Fabricius known from Albania. This expedition collected 114 individuals of 31 species, 23 species of Avhich were new in the fauna of Albania. In addition, 9 individuals of 7 species from the Museum of Natural History in Vienna and 2 individuals of 2 species from the author’s collection were studied, which disclosed 7 other first finds. Two species (A. argentata Smith and A. quadrimaculata Friese) are new in the Balkan peninsula, the latter being found for the first time in Europe. Now 45 species of Andrena are known from Albania. Material of 38 species was available to the author. What other species of Andrena may be expected in Albania is shown by a survey of all species that occur in the Balkan countries.